Effect of preoperative pneumococcal immunization on the incidence of respiratory infection in the postoperative period of cardiac surgery (Research, Society and Development, 2021)
Objective: To analyze whether the incidence of respiratory infections in the postoperative period of cardiac surgery is lower in patients immunized with the 13-valent pneumococcal conjugate vaccine. To study the main risk factors related to the development of infections in patients undergoing cardiac surgery. Methodology: 40 patients were included in the study, randomized 1: 1 to receive pneumococcal vaccine or placebo, 14 days before undergoing elective cardiac surgery. The incidence of infections in the 30 postoperative days was compared between groups. Results: There were 6 respiratory infections in the vaccine group and 2 in the placebo group (p=0.2024) and one death in the placebo group and none in the vaccine group (p=0.3173). Chronic obstructive pulmonary disease (p=0.003), diabetes mellitus (p=0.047) and peripheral arterial disease (p=0.0001) were listed as risk factors for the development of infections, which generated an increase in hospital stay (95% CI : 1.33- 7.13; p =0.0147) and ICU stay in the postoperative period (95% CI: 1.87- 33.45; p=0.0025). Conclusion: The application of pneumococcal vaccine 13v did not influence the development of postoperative pulmonary infections. Chronic obstructive pulmonary disease, diabetes mellitus and peripheral arterial disease were identified as risk factors for the development of infections, increasing the length of total hospital stay and time in the ICU.